KALIMAT TANYA DALAM FILM PITCH PERFECT KARYA JASON MOORE - Londok, Aprilia Fenria Ireine (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This study, entitled â€œThe Interrogative Sentence in The Filmâ€ Pitch Perfect by Jason Moore, is aimed at identifyng and analyzing the interrogative sentence found in the film. The data have been collected by focusing on the conversation among the characters in the film and analyzed based on Aarts and Aartsâ€™ concept. Interrogative sentence is a sentence that contains subject and open with an auxiliary verb or a wh-word. Interrogative sentence which is open with an auxiliary verb is called yes/no question and another type of yes/no question that consist of statement appended to the question is called question tag. The result shows that there are three forms of interrogative sentence in English used in the film. Those are yes/no question, question tag, wh- question. Yes/No question can be answered by yes/no, question tag is a question that is added at the end of sentence, wh-question begins with a question word such as : who, what, when, where, why, how, whom, or which. In this film the characters or use interrogative sentence without a question word but with rising intonation. According to its functions in communications, interrogativeÂ sentence can be functioned as question and reques. Â Keywords: Interrogative Sentence, Grammatical Analysis, Film Pitch Perfect.